2016
DOI: 10.1371/journal.pone.0163324
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Inhibitory Peptide as a Novel Therapy to Control Chronic Visceral Hypersensitivity in a Rat Model

Abstract: BackgroundThe pathogenesis of multiple chronic visceral pain syndromes, such as irritable bowel syndrome (IBS), is not well known, and as a result current therapies are ineffective. The objective of this study was to investigate the effect of spinal protein kinase M zeta (PKMζ) on visceral pain sensitivity in rats with IBS to better understand the pathogenesis and investigate the effect of zeta inhibitory peptide (ZIP) as a therapy for chronic visceral pain.MethodsVisceral hypersensitivity rats were produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Brain‐derived neurotrophic factor increases PKMζ protein expression at the spinal synapses in a chronic allodynia pain state (Melemedjian et al, ). We previously found that PKMζ or pPKMζ expression increased in the hippocampus (Chen et al, ) or the spinal segments of IBS‐like model rats (Tang et al, ). Furthermore, we found that BDNF expression was enhanced in NMS rats; is it possible that BDNF could regulate PKMζ expression?…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Brain‐derived neurotrophic factor increases PKMζ protein expression at the spinal synapses in a chronic allodynia pain state (Melemedjian et al, ). We previously found that PKMζ or pPKMζ expression increased in the hippocampus (Chen et al, ) or the spinal segments of IBS‐like model rats (Tang et al, ). Furthermore, we found that BDNF expression was enhanced in NMS rats; is it possible that BDNF could regulate PKMζ expression?…”
Section: Resultsmentioning
confidence: 94%
“…Male Sprague–Dawley rats were provided from the Department of the Experimental Animal Center of Fujian Medical University. NMS was established as described previously (Tang et al, ). Briefly, on postnatal 3–21 days neonates were separated from their mothers for 180 min every day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separation of pups from their dams was conducted daily for 6 h as of postnatal day 2 to15, with distinction from studies of MS models established by separating pups from their dams 3 h daily. As per their findings, separation for 3 h daily can develop somatic and visceral hyperalgesia as well [ 49 52 ]. Nevertheless, we have recognized that exposure to MS 3 h daily could not develop visceral hypersensitivity in adulthood, whereas separation for 6 h daily could successfully induce visceral hypersensitivity, which was contrary to the abovementioned results [ 51 , 52 ] and consistent with our previous reports [ 53 ].…”
Section: Discussionmentioning
confidence: 90%
“…AWR and threshold pressure of CRD which induced the first contraction of abdominal muscles were assessed in a blinded manner. As previous studies [ 18 , 23 ], rats were anaesthetized by isoflurane using an anesthetic equipment (AS-01-0007, Summit, USA). Connected with syringe and sphygmomanometer, a balloon was inserted into the colorectum after lubrication.…”
Section: Methodsmentioning
confidence: 99%